A FEM punch-through IGBT model using an efficient parameter extraction method - Rui Chibante (2005)
A Finite Element physics-based punch-through IGBT model is presented. The model's core is based on solving the Ambipolar Diffusion Equation (ADE) trough a variational formulation, resulting in a system of ODEs. The approach enables an easy implementation into a standard circuit simulator SPICE by means of an electrical analogy with the resulting system of ODEs, solved as a set of current controlled RC nets that describes charge carrier distribution in low-doped zone. The issue of parameter extraction for physics-based IGBT models is also addressed. An optimisation-based algorithm enabling an efficient parameter extraction method for IGBT model is discussed. Model is validated comparing experimental and simulated results.